The Influence of Leadership Styles on Employees Performance in Bole Sub City Education Sectors-Addis Ababa, Ethiopia (International Journal of Innovative Research in Engineering & Management, 2022)
The purpose of the study was to assess the  practices of leadership styles that influence employees’ job  performance. In the case of the Bole sub-city education  sector, Addis Ababa, Ethiopia. The results of the research  were mixed. Some are positive results and some are  negative results. For a long time, most research scholars  and academicians have taken various leadership styles that  are conducted under different leadership theories. This  study has selected leadership styles such as  transformational, transactional, Autocratic and servant  leadership styles as independent variables that are supposed  to have a direct effect on employees’ job performance  which is the dependent variable. A questionnaire was  developed using different past literature which is similar to  this title on the study of leadership style and employees  performance. A sample of 110 respondents was recruited  using simple random probability sampling techniques.  Collected data for this research was recorded and analysed  using SPSS 20.0. the result of the research shows that  transformational and servant leadership behaviours  positively and significantly influence employees’  performance at the workplace. And the remaining  Autocratic and transactional leadership behaviours are not  significant in influencing employees’ performance.  Depending on the finding researchers concluded that  transformational and servant leadership behaviours directly  influence employee performance. Managers or leaders and  also team leaders in any governmental or private  organization should find ways to use especially servant  leadership behaviour to improve employee job  performance, especially among department heads, district  level education heads; district level education heads and  officers in the sub-city.
Keywords: Leadership Styles; Autocratic; Transformational; Transactional; Servant; Employee Performance